A facile in-situ activation of protonated histidine-derived porous carbon for electrochemical capacitive energy storage - Thanh-Nhan Tran; Kim, Hwa Jung; Samdani, Jitendra S.; Hwang, Jun Yeon; Ku, Bon-Cheol; Lee, Jae Kwan; Yu, Jong-Sung (한국공업화학회, 2019)
A unique and effective synthesis approach to tune the structural and electrochemical properties of carbon materials (CMs) is demonstrated by template-free one-step pyrolysis of protonated histidine (His) containing each of different inorganic acids (HAS) such as HI, HBr, HCl, HNO3, H2SO4, and H3PO4. In particular, the (H3PO4)His-CM possesses high specific surface area, high capacitance, superior energy density and power density along with excellent cycle life. Such excellent electrochemical performance of (H3PO4)His-CM is attributed to the tunable structural properties of the precursor, where H3PO4 plays dual roles of in-situ activation and additional P doping in the carbon skeleton. (C) 2019 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.